2015
DOI: 10.1073/pnas.1423009112
|View full text |Cite
|
Sign up to set email alerts
|

Purinosome formation as a function of the cell cycle

Abstract: The de novo purine biosynthetic pathway relies on six enzymes to catalyze the conversion of phosphoribosylpyrophosphate to inosine 5′-monophosphate. Under purine-depleted conditions, these enzymes form a multienzyme complex known as the purinosome. Previous studies have revealed the spatial organization and importance of the purinosome within mammalian cancer cells. In this study, time-lapse fluorescence microscopy was used to investigate the cell cycle dependency on purinosome formation in two cell models. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 37 publications
7
102
0
Order By: Relevance
“…Immunofluorescence has demonstrated purinosome formation on the endogenous level and provided evidence that the observed compartmentalization is not a consequence of overexpression due to transient transfection [6, 34-36]. Additionally, particle characterization in transient transfected models demonstrated that these enzyme clusters are distinct in size and cell density from processing bodies (P-bodies), stress granules, and aggresomes (Box 2) [37]. Using G3BP as a stress granule marker and gp250 and gp170* as aggresome markers, the purinosome enzyme cluster did not colocalize [38].…”
Section: Discovery Of a Metabolon In Purine Metabolism – The Purinosomementioning
confidence: 99%
See 3 more Smart Citations
“…Immunofluorescence has demonstrated purinosome formation on the endogenous level and provided evidence that the observed compartmentalization is not a consequence of overexpression due to transient transfection [6, 34-36]. Additionally, particle characterization in transient transfected models demonstrated that these enzyme clusters are distinct in size and cell density from processing bodies (P-bodies), stress granules, and aggresomes (Box 2) [37]. Using G3BP as a stress granule marker and gp250 and gp170* as aggresome markers, the purinosome enzyme cluster did not colocalize [38].…”
Section: Discovery Of a Metabolon In Purine Metabolism – The Purinosomementioning
confidence: 99%
“…Using G3BP as a stress granule marker and gp250 and gp170* as aggresome markers, the purinosome enzyme cluster did not colocalize [38]. Finally, Western blot analysis found the levels of all six enzymes remained unchanged as the composition of the culturing media was switched [37]. Together, these conclusions further define the purinosome as a unique cellular body and not an artifact of transient transfection.…”
Section: Discovery Of a Metabolon In Purine Metabolism – The Purinosomementioning
confidence: 99%
See 2 more Smart Citations
“…The spatial organization of these enzymes in cells is referred to as a purinosome and has been the subject of recent reviews [9, 10]. Purinosome assembly has shown to be a reversible phenomenon whose phenotype is largely predominant when cellular conditions result in a high purine demand, such as in the G 1 -phase of the cell cycle [6, 11]. Cellular conditions favoring purinosome formation were also shown to enhance the metabolic flux of the de novo purine biosynthetic pathway suggesting that the two observations are connected—a generalized hypothesis surrounding metabolon formation in cells [12].…”
Section: Introductionmentioning
confidence: 99%